If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -52 = 6m + -10 Reorder the terms: -52 = -10 + 6m Solving -52 = -10 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -52 + -6m = -10 + 6m + -6m Combine like terms: 6m + -6m = 0 -52 + -6m = -10 + 0 -52 + -6m = -10 Add '52' to each side of the equation. -52 + 52 + -6m = -10 + 52 Combine like terms: -52 + 52 = 0 0 + -6m = -10 + 52 -6m = -10 + 52 Combine like terms: -10 + 52 = 42 -6m = 42 Divide each side by '-6'. m = -7 Simplifying m = -7
| 3+5(a+2)+a= | | 5x+6x=55+x | | x+6y-2=0 | | 65-3x=24x+17 | | (2x-15)=(4x-19) | | 11.9squared+14.7squared=csquared | | -10(-7+k)=10 | | 2x=49 | | (6x)=(5x+16) | | 3p-16=7+2(-8p-3) | | 26k=12 | | 6n(n+3)=12n-12 | | (4x-9)/3+6(x/6)=6(x/2)-2 | | 4x-8=69+7x | | 68m+13=13+8m | | 5x+8x-24=180 | | 7y-8y+5y+y^2-1+2y^2= | | (X-14)=(x+84) | | 6=.83(12-b)+1 | | 25+x=x*3 | | 6=.8333(12-b)+1 | | 5y+7-3y=-17+8 | | 2t+11=t-13 | | x(5)+x+7=65 | | w/2=13/4 | | (9x-1)=(7x+3) | | 4-4(3x-3)=-4 | | w/2=1-3/4 | | 38+3y-12=13y-9-5y | | 10(x+3)=30 | | -18c=30 | | 12+54x=25x-110+4 |